Enhancing Physics Experience: VIRRE (Virtual Reality of Renewable Energy) to Increasing Concept Understanding and Learning Motivation in Secondary Education - Anggaryani, Mita; Citra, Nina Fajriyah (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2024)
This research aims to develop VR in renewable energy materials (VIRRE) to increase students’ concept understanding and learning motivation. This research used Research and Development (R&D) method through ADDIE development model. Validation was carried out to determine the feasibility of VIRRE, then implemented in secondary school students by using problem-based learning model throughout three meetings. Research data was collected through questionnaires and pretest-posttest during classroom learning. The results show that VIRRE has a validity percentage of 94.07% with very valid criteria. The effectiveness of VIRRE media in increasing students' concept understanding and learning motivation is included in medium criteria with n-gain scores of 0.52 and 0.33 respectively. Additionally, VIRRE usage in learning activities showed the most improved indicator of concept understanding and aspect of learning motivation, namely classifying and self-confidence respectively. Moreover, the result indicates that both concept understanding and learning motivation are related to each other, once students are motivated to learn the subject, they can achieve a great understanding of its concept. VIRRE received very good responses from students in aspects of learning activities, materials, and media use with average percentages of 82.22%, 82.7%, and 84.23% respectively. Thus, VR could be an alternative media learning to support educators in delivering physics materials, which are viewed as complicated concepts according to the students.